Pengaruh Suasana Kafe Terhadap Niat Kunjungan Ulang Dengan Kepuasan Pelanggan Sebagai Variabel Mediasi: Studi Kasus: Pemutaran Musik Instrumental Di Jco Reserve Jalan Jenderal Sudirman, Kota Bogor - Saefudin Zuhdi; Wimpi Srihandoko; Fandy Sanjaya (Jurnal Ilmiah Pariwisata Kesatuan, 2026)
Using customer satisfaction as a mediating variable, this study was carried out at JCO Reserve to investigate the impact of café atmosphere on revisit intention. The study's foundation is the idea that creating a welcoming and cosy café atmosphere is crucial to boosting patron satisfaction and encouraging repeat business. Customers of JCO Reserve were given questionnaires to complete in order to gather data for this quantitative research project. Purposive sampling was used in the sampling procedure. Additionally, Structural Equation Modelling (SEM) with the Partial Least Square  (PLS) approach was used to process and analyse the data. The results of this study demonstrate that customer happiness is positively and considerably impacted by café atmosphere. Additionally, it was discovered that the intention to return was positively and significantly impacted by customer satisfaction. The findings also show that revisit intention is positively and significantly impacted by café atmosphere. Furthermore, it has been demonstrated that the association between café atmosphere and intention to return is mediated by customer satisfaction. According to the study's findings, enhancing a café's ambience, especially with regard to music, can boost patron satisfaction, which in turn promotes the intention to return